Effects of vehicle age on fuel economy for urban driving cycles - Fauziana Lamin; Afiqah Omar; Noor Kamaliah Alias; Azhar Hamzah; Syaiful Bahri Ismail; Md Razif Md Berhannudin; Mohd Redza Abdul Razak (Penerbit Universiti Kebangsaan Malaysia, 2023)
Optimal service life is among the most crucial determinant factors in vehicle life-cycle planning and management. A multi-dimensional operational cost covering asset acquisition, operating, and maintenance until disposal requires a strategic analysis to ensure economic vehicle ownership. The economic service life issue is more prominent for transportation management with a high number of vehicle ownership capacity. Accordingly, two-year fuel consumption data of a local authority passenger vehicle fleet that is mainly used for urban driving cycles was retrieved. Taking advantage of the actual fuel consumption data, this study explores the effect of vehicle age on fuel economy. Based on the fuel consumption and odometer reading, the average fuel consumption profile reveals a significant decrease following the addition of passenger vehicle age. In particular, vans showed a negative gradient in fuel consumption per year of -0.8 L/year, the highest decrement rate as compared to cars, -0.5 L/year and SUVs, -0.19 L/year. In terms of fuel economy, a comparatively low performance was recorded by cars, which is 9.38 km/L, as compared to SUVs, 27.05 km/L. Nevertheless, the fuel economy degradation for SUVs is 35% higher compared to cars. This result confirms the hypothesis that the longer the vehicle ages, the lower its fuel economy. Interestingly, this study suggests seven years as the start of a decline in the passenger vehicle fuel economy, independent of vehicle type. This research framework could be replicated to a bigger data scale for the economic vehicle service life determination in Malaysia that currently continues to be voluntary. It is vital as part of the basis for the future establishment of the national ELV definition.